KARAKTERISTIK PERTUMBUHAN SEMAI BINUANG ASAL PROVENAN PASAMAN SUMATERA BARAT - Tri Pamungkas Yudhohartono; Rizki Ary Fambayun (Jurnal Pemuliaan Tanaman Hutan, 2012)
Binuang is fast growing species which is native in Indonesia. This research is purposed to know the role of genetic variation to characteristic of binuang seedling at the age of 6th and 10th month from several mother trees from Pasaman, West Sumatera provenances in nursery. This research was arranged in Completely Randomized Design (CRD) with 22 pohon indukes and 5 replications. Each replication comprises 9 seedlings. Totally, there are 990 seedlings. The results showed that high genetic variation have effected observed traits of binuang seedlings. It showed by the high genetic variation of height, diameter and sturdiness quotient among binuang mother trees. Seedlings having the high value of diameter and height value of seedlings at all observation ages were from the same mother namely mother tree 17. Seedlings had the lowest average diameter at all observation ages were from the same mother namely mother tree 6. Whereas, seedlings had the lowest average height at 6 and 10 months were from mother tree 9, 7 and 6. Value of sturdiness quotient of seedlings from all mother trees at 6 and 10 months was above or classified high. Mother tree had the lowest sturdiness quotient at all observation ages was mother tree 19. The value of sturdiness quotient decreased along with increasing the age of binuang seedlings